Imidazolidin-4-ones via (3+2) cycloadditions of aza-oxyallyl cations onto (E)-N-arylideneanilines - Eyilcim, Oznur; Issever, Sezin; Ocal, Nuket; Gronert, Scott; Erden, Ihsan (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In the course of our studies on the chemistry of oxyallyl species we uncovered a new (3+2) cycloaddition of aza-oxyallyl systems, generated in situ from N-benzyloxy-2-chloroamides in the presence of NEt3, onto N-arylimines yielding imidazolidin-4-ones in moderate to good yields. The cycloadditions are regioselective. Computational modeling using DFT at the M062x/6-311+G** level is in support the observed regioselectivities. Although the path to the trans imidazolin-4-one is favored, the cis product is preferred by almost 8 kcal/mol and could be formed by base-catalyzed epimerization. All products were isolated by chromatography and characterized by means of their FTIR, NMR and HRMS data. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Aza-oxyallyl; Aza-cyclopropanone; N-arylimine; (3+2) cycloaddition; Imidazolidin-4-one; ALLENE OXIDE; AZAOXYALLYL CATIONS; SINGLET OXYGEN; INTERMEDIATE; CHEMISTRY; ACCESS